2022
DOI: 10.1186/s12902-022-01116-1
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ disease and papillary thyroid carcinoma: case report and literature review of a single academic center

Abstract: Background Graves’ disease (GD) and papillary thyroid cancer (PTC) can be concomitant. The existence of a link between these entities has long been investigated, but a clear correlation hasn’t been established. We report a case of GD resistant to medical treatment in which surgery revealed unsuspected PTC and we aim to study the prevalence of PTC in Graves’ disease, its clinical characteristics and review of the literature. Case presentation Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Therefore, even in Graves surgery, maintaining specimen integrity is crucial. In previous studies, 33,34 a fragmented specimen could cause tumor seeding or compromise the pathologic examination 35,36 . Our series used a 1- to 2-cm wound at the right axillary skin fold to remove the larger specimen and maintain the oncologic principle of surgery without compromising the patient’s esthetic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even in Graves surgery, maintaining specimen integrity is crucial. In previous studies, 33,34 a fragmented specimen could cause tumor seeding or compromise the pathologic examination 35,36 . Our series used a 1- to 2-cm wound at the right axillary skin fold to remove the larger specimen and maintain the oncologic principle of surgery without compromising the patient’s esthetic appearance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 75 ] These conclusions are consistent with those of other studies. [ 76 , 77 ] However, the mechanisms underlying the development of thyroid nodules and cancer in patients with GD remain unclear. Some studies have proposed a crucial role of thyroid-stimulating immunoglobulin in this process.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an ongoing debate regarding whether TRAb levels positively or negatively correlate with the incidence of thyroid cancer in patients with GD. [ 75 , 77 , 78 ] Future research should provide evidence to substantiate this correlation and unveil the underlying mechanisms to achieve early prediction, diagnosis, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, research from the University of Chicago indicated that among patients with GD who underwent total thyroidectomy, 20% were diagnosed with both GD and thyroid cancer. These cases were primarily middle-aged females with positive TSI, and most of them presented with unifocal microcarcinomas[ 12 ]. Local data at Saudi Arabia showed that majority of patients with GD underwent total thyroidectomy because of failed antithyroid drugs and severe ophthalmopathy[ 13 ], while a retrospective study in Saudi Arabia demonstrated that only 5% of patients with thyroid cancer undergoing thyroidectomies were identified as hyperthyroid, with limited details regarding cancer characteristics[ 14 ].…”
Section: Discussionmentioning
confidence: 99%